2019
DOI: 10.1093/ehjcvp/pvz016
|View full text |Cite|
|
Sign up to set email alerts
|

Oral anticoagulation in patients with non-valvular atrial fibrillation and a CHA2DS2-VASc score of 1: a current opinion of the European Society of Cardiology Working Group on Cardiovascular Pharmacotherapy and European Society of Cardiology Council on Stroke

Abstract: Oral anticoagulation in patients presenting with non-valvular atrial fibrillation and a CHA2DS2-VASc score of 1 (CHA2DS2-VASc of 2 in women) remains a challenging approach in clinical practice. Therapeutic decisions need to balance the individual benefit of reducing thromboembolic risk against the potential harm due to an increase in bleeding risk in this intermediate risk patient population. Within the current opinion statement of the European Society of Cardiology working group of cardiovascular pharmacother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 61 publications
0
26
0
9
Order By: Relevance
“…В 2019 году опубликован документ, содержащий мнение рабочей группы экспертов по кардиоваскулярной фармакотерапии Европейского кардиологического общества и совета Общества Кардиологов по инсульту [5]. Этот документ содержит алгоритм принятия решения о назначении антикоагулянтов у больных с 1 баллом (кроме женского пола) по шкале CHA 2 DS 2 VASc, основанный на сопоставлении риска инсульта и кровотечения.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…В 2019 году опубликован документ, содержащий мнение рабочей группы экспертов по кардиоваскулярной фармакотерапии Европейского кардиологического общества и совета Общества Кардиологов по инсульту [5]. Этот документ содержит алгоритм принятия решения о назначении антикоагулянтов у больных с 1 баллом (кроме женского пола) по шкале CHA 2 DS 2 VASc, основанный на сопоставлении риска инсульта и кровотечения.…”
Section: Discussionunclassified
“…Этот документ содержит алгоритм принятия решения о назначении антикоагулянтов у больных с 1 баллом (кроме женского пола) по шкале CHA 2 DS 2 VASc, основанный на сопоставлении риска инсульта и кровотечения. При наличии ≥2 баллов риска кровотечения, т. е., при преобладании риска кровотечения над риском инсульта следует воздержаться от терапии антикоагулянтами, корригировать потенциально модифицируемые ФР кровотечения (АГ, применение нестероидных противовоспалительных средств, злоупотребление алкоголем), после чего вновь провести оценку риска кровотечения и сопоставить с риском инсульта [5] (рис. 1).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Warfarin or non-vitamin K antagonist oral anticoagulants (NOACs) are recommended for patients at high risk of stroke. However, the abovementioned two scoring systems do not take into account other potential risk factors, such as renal function impairment, rheumatoid arthritis, obesity or smoking, as well as clinically accessible laboratory indicators, imaging values and other parameters [4,5]. Friberg et al [6] have shown that clinically diagnosed heart failure is not an independent risk factor for stroke in AF patients.…”
Section: Introductionmentioning
confidence: 99%